Spreadsheet Conditional Formatting: An Untapped Resource for Mathematics Education - Sergei Abramovich; Stephen Sugden (Spreadsheets in Education, 2005)
Electronic spreadsheets have been with us for almost 25 years. In that period, innovative educators have found many ways in which this ubiquitous class of software may be leveraged in support of learning, especially in mathematics and the physical sciences. Conditional formatting is a relatively recent feature of the modern graphical spreadsheet, and may be viewed as a generalization of the accounting procedure of indicating debits by red ink and other amounts in black. The paper discusses advances in technology-enabled pedagogy made possible by this seemingly trivial feature of the modern spreadsheet program.